2018
DOI: 10.1097/md.0000000000010847
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is not associated with renal function decline in community-dwelling elderly adults

Abstract: Adiponectin secreted by adipocytes plays an important role in the regulation of glucose and fatty acid metabolism. Contrary to findings in patients with chronic kidney disease (CKD), no prospective data about the association of serum adiponectin with renal function decline in the general population have yet appeared. Our objective was to analyze the relationship of total and high molecular weight (HMW) adiponectin with renal function decline as measured by cystatin C in community-dwelling elderly adults withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The leptin levels were quantified using a human leptin radioimmunoassay kit (EMD Millipore Corporation, Billerica, MA) (26). The adipokine adiponectin was measured using a human adiponectin latex kit (LSI Medience Corporation) (27).…”
Section: Blood Analysismentioning
confidence: 99%
“…The leptin levels were quantified using a human leptin radioimmunoassay kit (EMD Millipore Corporation, Billerica, MA) (26). The adipokine adiponectin was measured using a human adiponectin latex kit (LSI Medience Corporation) (27).…”
Section: Blood Analysismentioning
confidence: 99%
“…Previous epidemiological studies showed inconsistent results in the causal relationship between serum ADPN and eGFR 7‐12 . Traditional epidemiological studies are easily interfered with by confounders, even when these studies adjust for all known confounders, but unknown confounders are difficult to adjust for.…”
Section: Discussionmentioning
confidence: 99%
“…The ADPN may improve eGFR through insulin sensitivity, anti‐atherosclerosis and anti‐inflammatory effects. Some previous epidemiological studies have shown a negative correlation between serum ADPN and eGFR reduction, 7‐10 but this result cannot be verified in other epidemiological studies 11,12 . Therefore, the relationship between serum ADPN level and eGFR remains controversial.…”
mentioning
confidence: 93%
“…Inverse associations were also observed among adiponectin levels and SAT, VAT, total body fat, and lean body mass [ 100 ]. Moreover, studies suggest a negative correlation between adiponectin levels and hand-grip [ 101 ]. Adiponectin may also affect bone turnover.…”
Section: Adipokines and Their Influence On Pathogenesis Nutritional D...mentioning
confidence: 99%